Anaemia, Dyslipidaemia and Electrolytes Imbalance in Type 2 Diabetes Mellitus: An analytical Cross-Sectional Study - Alhwij, Ismail; Ali Aborkis; Abdulhakim Alhaaj; Esra Ben Noor; Mansour Ghazi; Mohmmed Abu Weden; Zohor Mansour (AlQalam Journal of Medical and Applied Sciences, 2024)
Type 2 diabetes mellitus (T2DM) is characterized by chronic hyperglycaemia resulting from defects in insulin secretion and/or insulin action and metabolic disorders of protein and lipids. Diabetic dyslipidaemia is a risk factor of the early development of coronary heart disease (CHD). Electrolyte imbalance also are common in diabetic patients and may be associated with increased morbidity and mortality. Furthermore, Anaemia in diabetic patient has a significant adverse effect on quality of life. Therefore, early detection of anaemia, dyslipidaemia and electrolyte imbalance may reduce the prevalence of complications in T2DM. This study was carried out to assess the prevalence and correlation of anaemia, dyslipidaemia, electrolyte imbalance in T2DM. A number of 50 T2DM patients’ demographic, biochemical and clinical data was collected from Zliten Medical Centre, Diabetes and Endocrinology Centres in Alkhoms & Zliten and Bin Haider Medical Laboratory. The raw data was classified and then analysed by the SPSS software. The results show that hypomagnesaemia is found to be prevalent pattern of electrolyte imbalance in T2DM patients (42/50) 84%. Hypertriglyceridemia (25/50) 50%, high VLDL (25/50) 50% and high LDL- cholesteraemia (20/50) 40%. Anaemia is shown to be endemic in T2DM patients which was determined by Hb level and found to be (39/50) 78%. Furthermore, T2DM was found to be uncontrolled in almost all of the study’s patients (49/50) 98%. In conclusion, anaemia, dyslipidaemia is very common in our study and high electrolyte imbalance is only represented by hypomagnesaemia. يتميز داء السكري من النوع الثاني بارتفاع سكر الدم المزمن الناتج عن عيوب في إفراز الأنسولين و/ أو عمل الأنسولين واضطرابات التمثيل الغذائي للبروتينات والدهون. يعد عسر دهون الدم السكري أحد عوامل الخطر للتطور المبكر لأمراض القلب التاجية. اعتلال الألكتروليتات أيضًا شائع لدى مرضى السكري وقد يترافق مع زيادة معدلات امراضية السكري ومعدل الوفيات. علاوة على ذلك ، فإن فقر الدم لدى مرضى السكري له تأثير سلبي كبير على حياة المرضى. لذلك ، فإن الاكتشاف المبكر لفقر الدم ، وعسر دهون الدم ، اعتلال الألكتروليتات قد يقلل من انتشار المضاعفات لمرضى السكري. أجريت هذه الدراسة المقطعية التحليلية لإظهار انتشار فقر الدم ، وعسر دهون الدم ، و اعتلال الألكتروليتات لمرضى السكري من النوع الثاني. تم جمع عدد من البيانات الديموغرافية والكيميائية الحيوية والسريرية لـ 50 مريض بالسكري من مركز زليتن الطبي ومراكز السكري والغدد الصماء ومختبر بن حيدر الطبي في بلديتي الخمس وزليتن. صنفت البيانات الأولية ثم حللت بواسطة برنامج الحزمة الإحصائية للعلوم الاجتماعية. أظهرت نتائج هذه الدراسة أن نقص المغنسيوم في الدم هو النمط السائد من اعتلال الألكتروليتات لمرضى السكري حيث كانت النسبة 84% (42/50).كذلك نسبة ارتفاع الدهون الثلاثية في الدم كانت 50% (25/50) ، ارتفاع الدهون البروتينة المنخفضة جدا ايضاً 50% (25/50)، وارتفاع الكولسترول الكلي في الدم 40% (20/50). أظهرت هذه الدراسة ايضاً أن فقر الدم منتشر بشكل كبير جدا في مرضى السكري والذي تم تحديده بواسطة مستوى الهيموجلوبين والذي كانت نسبته 78% (39/50). علاوة على ذلك ، وجد أن السكري غير مسيطر عليه لجميع مرضى الدراسة تقريبًا 98% (49/50). في الختام ، فإن فقر الدم ، وعسر دهون الدم شائعان جدًا في دراستنا اما اعتلال الألكتروليتات فان نقص مغنسيوم الدم هو السائد